ASSOCIATION OF AGE AND GENDER IN TEETH WITH ATTRITION REQUIRING ROOT CANAL TREATMENT - A RETROSPECTIVE ANALYSIS - K, Kiran; K, Sowmya; Narayan, Vivek (International Journal of Psychosocial Rehabilitation, 2020)
Attrition is a wasting disease of the teeth caused mainly due to tooth-to-tooth contact. The friction caused by teeth rubbing against each other can wear away the biting surface of the teeth. The treatment for attrition varies based on the extent of tooth structure loss. Excessive loss of tooth structure can lead to pain and periapical changes and might require root canal treatment for its management. The aim of this study was to evaluate the number, teeth, age, and gender distribution of teeth with attrition that required root canal treatment. In this retrospective study, case records of patients who visited Saveetha Dental College from June 2019 to April 2020 were evaluated. Data of patients with attrited teeth that required root canal treatment was collected, tabulated, and imported to SPSS for statistical analysis. Fisher’s exact test was done to find the association, and the significance level was set at 0.05. Severe attrition requiring root canal treatment was more common in the older age group. Mandibular molars had more attrition than other teeth. Males showed a higher number of attrited teeth requiring root canal treatment than females in the age group less than 40 years (Fisher's exact P value = 0.006). Within the limitations of the study, it can be concluded that severe attrition that requires endodontic treatment increases with age and is more common in males.